Regional disparities in the distribution of public and private healthcare facilities in South Korea - Jiyu Park; Byeongyun Jeon; Eun Lee (PLoS ONE, 2025)
Unequal healthcare facility distributions remain a critical concern in South Korea, where medical resources are disproportionately concentrated in metropolitan areas, leading to disparities in the availability of services between regions. These spatial disparities are also influenced by broader contextual factors such as socioeconomic inequality and transportation infrastructure, which interact with access to care. Focusing on the spacial dimension of these disparities, this study investigates the spatial distribution of public and private medical facilities by analyzing their allocation patterns to identify underlying principles associated with these distributional trends, using a cost optimization approach rooted in statistical physics. By employing concentration index (CI), we quantify regional inequalities in general hospitals and clinics. Additionally, using scaling exponents, we aim to understand the principles underlying the distributional differences between public and private healthcare facilities and examine whether these differences vary across medical specialties. Our findings reveal that private hospitals and clinics exhibit stronger correlations with population density, reflecting commercial-like allocation patterns, while public institutions demonstrate more even spatial distributions. However, some essential medical specialties, including emergency medicine, pediatrics, and obstetrics and gynecology, are sparsely distributed in public sectors. Furthermore, temporal scaling exponent analysis suggests that private medical institutions are gradually intensifying their commercial characteristics, potentially exacerbating future disparities. These results provide a comprehensive understanding of the distribution patterns of healthcare facilities across regions and establishment types, while uncovering the underlying principles that shape these patterns based on medical specialties, providing valuable insights to inform future resource allocation strategies in the health sector.